(untitled) - The World Bank in VietNam (WB) (Ha Noi, 2004)
The Natural Disaster Risk Management Program Project adopts an innovative approach, providing support primarily for disaster prevention and mitigation measures, including at the community level where vulnerability is often greatest, to reduce the impact of natural hazards on Vietnam's development process. It will build on the Bank's recent experiences in disaster prevention and vulnerability reduction. The project will directly support sustainable development which is a key theme of the FY03-06 Country Assistance Strategy (CAS) for Vietnam. The project will focus on the most severely affected provinces, mainly the frequently and deeply flooded areas of the Mekong Delta and the North Central Provinces, through four components: 1) Prevention and Mitigation Investments - this component will support priority prevention and mitigation medium-scale investment subprojects to reduce disaster risks, and strengthen prevention capabilities in areas most affected by floods and storms. Specifically the component will support: investments focused on the construction and rehabilitation of flood and storm-control infrastructure; investments for upgrading flood and storm monitoring, modeling and prediction capabilities, and enhance early warning and response systems; and, the strengthening of the institutional process and capacity for selecting sub-project investments. 2) Community-based Disaster Risk Management - through four types of activities: a) commune-level capacity building, further supporting the development of participatory planning; b) monitoring and evaluation, strengthening the partnership between poor communities; c) community structural investment sub-projects; and, d) community non-structural investment sub-projects. 3) Post-Disaster Reconstruction Support - in support of post-disaster reconstruction of small-size public infrastructure, supporting fast recovery and reducing the diversion of limited public investment resources from new development investments into reconstruction. 4) Project Management and Institutional Strengthening - through the provision of technical assistance for implementing agencies, to strengthen institutions and enhance risk management capability.
Quản lý và giảm nhẹ thiên tai,Dự báo và quản lý thảm họa
Keywords: Phòng chống thiên tai và Chương trình giảm nhẹ thiên tai; Natural Disaster Prevention and Mitigation Programme